Pola Tahanan Jenis dan Konduktivitas Batuan Mengandung Mineral Radioaktif di Botteng dan Takandeang, Mamuju, Sulawesi Barat - Muhammad, Adi Gunawan; Indrastomo, Frederikus Dian; Sukadana, I Gde (EKSPLORIUM, 2017)
The general investigation activities of radioactive minerals in Mamuju Area, West Sulawesi is a respon of the environmental radioactivity measurement result, which shows the existence of high radioactivity value. High radioactive mineral content found in Botteng and Takandeang Villages. From the outcrops, they composed of leucite-basalt rocks; meanwhile the subsurface characteristics of this area are unknown. To characterize the subsurface geology, related to uranium and thorium mineralization in Botteng and Takandeang area, geophysical measurement conducted using resistivity and Induced Polarization (IP) methods. The measurements carried out using Wenner and dipole-dipole configurations. The measurements started with the creation of six measurement paths where three lines: GF/BTGY-01, GF/BTGK-02, and GF/BTGK-04 are in Botteng and three other lines: GF/TKDK-01, GF/TKDK-07 and, GF/TKDY-06 are in Takandeang. Measurements conducted by crossing the surface radiometric anomaly distribution. The result showed anomaly occurences on autobreccia distribution in GF/TKDY-6, GF/TKDK-07, and GF/BTGK-04 locations. Several mineralization indication on surface identified in GF/BTGK-0, and GF/TKDK-01 sections, charaterized by chargeability anomalies more than 25.14 ms and 81.4 ms respectively. All significant anomalies are recomended as drilling location.